Following a self-guided trail within an accredited US campus arboretum: The use of an AI-based app for tree identification and tour enrichment - Kadak, Merve Kalayci (BioResources, 2025)
Being in an urban or developed area can adversely affect human well-being. On the other hand, human well-being is supported by recreational activities, which are often carried out outside, particularly in natural areas. Most research on such topics has focused on non-urban/non-developed areas, for which the term ecosystem services describes the direct and indirect benefits that people may receive. In developed regions, limited access to natural features can hinder these benefits. This study explored the specific case of a tree-walking route located within a developed campus in the US. This route is noteworthy for its diverse collection of 40 distinct woody species, which contributes to the campus’s green infrastructure. Two on-site observations were carried out to visually document the trees on the route and to understanding ecological value. An AI-based mobile application, ‘Picture This’, was used to follow the route as a self-guided participant. The results indicate that it is possible to use the application as a guide with approximately 84% accuracy. Its accessibility enhances its potential as a free resource for researchers, students, and nature enthusiasts.